Chronopharmacokinetics of Methotrexate in Mice: Modulation by Administration of 5-Fluorouracil in Combination Chemotherapy - Graczyk Julita (Pteridines, 1996)
The basic pharmacokinetic parameters of MTX administered as monotherapy as well as in the combined therapy with simultaneous and prior administation of FU were investigated. The parameters were determined in the two-compartment open system on the basis of measurement of MTX levels in mice after i.p. administration of a single dose 20 mg/ kg of the drug. The FU dose was 20 mg/kg, too. The effect of the circadian rhythm on the kinetics of MTX have been taken into consideration. In one series of experiments the drugs were administered in the morning and in the other during midday hours . The statistical analysis of the obtained results showed the essential effect of the administration time on the pharmacokinetic parameters of MTX in mice. The statistical significal differences could be found: C max, AUC, CL, T0,5 . The differences in T0,5 , parameter resulting from coadministration of FU with the same circadian rhythm of MTX administration have been observed.